2016
DOI: 10.1093/icvts/ivw141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of negative pressure wound therapy followed by tissue flaps for deep sternal wound infection after cardiovascular surgery: propensity score matching analysis

Abstract: NPWT and tissue flaps may be favourable factors associated with reduced in-hospital mortality attributable to DSWI. NPWT as a bridge therapy to tissue flaps may play a major role in treating DSWI and improve the prognosis for patients with MRSA-infected DSWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
2
50
0
1
Order By: Relevance
“…Negative pressure wound therapy (NPWT) applies subatmospheric pressure to the surface of wound, removes excessive fluid, decreases wound edema, accelerates wound healing and granulation tissue formation, stabilises chest wall, increases sternal blood flow and has been shown to improve early and long term survival in patients with deep sternal wound infection. It has emerged as one of the most significant developments in the last two decades in the management of sternal wound infections [ 31 , 32 ]. All deep sternal wound infections and all limited sternal wound dehiscences not resulting in frank sternal instability should be treated in the first instance with negative pressure wound therapy and antibiotics.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative pressure wound therapy (NPWT) applies subatmospheric pressure to the surface of wound, removes excessive fluid, decreases wound edema, accelerates wound healing and granulation tissue formation, stabilises chest wall, increases sternal blood flow and has been shown to improve early and long term survival in patients with deep sternal wound infection. It has emerged as one of the most significant developments in the last two decades in the management of sternal wound infections [ 31 , 32 ]. All deep sternal wound infections and all limited sternal wound dehiscences not resulting in frank sternal instability should be treated in the first instance with negative pressure wound therapy and antibiotics.…”
Section: Reviewmentioning
confidence: 99%
“…In DSWI infected with MRSA, in particular, NPWT significantly reduced in-hospital mortality caused by DSWI (0 vs 52%, P = 0.003). Equally importantly, NPWT as a bridge therapy to tissue flaps may play a major role in treating DSWI and improve prognosis for patients with MRSA-infected sternal wounds [ 31 ]. Debreceni et al reported on 62 consecutive patients who underwent vacuum assisted wound closure (VAC).…”
Section: Reviewmentioning
confidence: 99%
“…It is worth noting that the deaths identified were not related to the therapy used, but to the severity of the infection. Consistent with these data, a retrospective observational study 19 evaluated the vacuum treatment for mediastinitis, and concluded that mortality rates were lower when compared to conventional treatment, and that by associating the vacuum with the use of flaps, the results were even better.…”
Section: Discussionmentioning
confidence: 73%
“…NPWT increases blood flow in the applied area and thus works in favor of any flap tissue remaining even though partially lost. This gives an opportunity to use the same flap to close the wound in most cases 6 , 10 . So, on the basis of this case, it can be suggested that the usage of NPWT promotes wound healing and contributes to the flap survival in the presence of infection and flap dehiscence in recurrent pilonidal disease.…”
Section: Discussionmentioning
confidence: 99%